Internet connectivity disruption in Iran (Iran) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Iran. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: IR-2026-0170. Severity: critical. Confidence: 67%